ANALISIS MOBILITAS SIRKULER KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Rivo Saputra; Ahyuni ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine the demographic characteristics of the perpetrators of circular mobility in Kamang Baru Subdistrict, Sijunjung District, the factors that influence the occurrence of circular mobility of Kamang Baru Subdistrict, Sijunjung District, the circular mobility patterns of Kamang Baru Subdistrict, Sijunjung District, and the remittances provided by the perpetrators of secular mobility who work for families left behind in the area of ​​origin. The research method used is a quantitative descriptive method to analyze the distribution of circular mobility between districts in Sijunjung Regency, Regency/City in West Sumatra and Provinces in Indonesia.Research Results Show that 1). Democratic characteristics of the perpetrators of circular mobility in productive age, dominated by women as much as 64.16%, dominant education of high school / equivalent as much as 55.5%, most jobs are students as much as 45%, 2). The biggest driving and pulling factor for perpetrators of circular mobility is education which is 55.83%, 3). The most dominant circular mobility pattern is the seasonal mobility pattern of 96.6%, 4). The number of remittances most given by circular mobility actors is <Rp. 1,000,000 which is 88.88%.